Circulating Inflamma-miRs as Potential Biomarkers of Cognitive Impairment in Patients Affected by Alzheimer’s Disease - Giuliani, Angelica; Gaetani, Simona; Sorgentoni, Giulia; Agarbati, Silvia; Laggetta, Maristella; Matacchione, Giulia; Gobbi, Mirko; Rossi, Tommaso; Galeazzi, Roberta; Piccinini, Gina; Pelliccioni, Giuseppe; Bonfigli, Anna Rita; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD), the most prevalent neurodegenerative disease in the growing population of elderly people, is still lacking minimally invasive circulating biomarkers that could facilitate the diagnosis and the monitoring of disease progression. MicroRNAs (miRNAs) are emerging as tissue-specific and/or circulating biomarkers of a number of age-related diseases, but evidence on AD is still not conclusive. Since a systemic pro-inflammatory status was associated with an increased risk of AD development and progression, we focused our investigation on a subset of miRNAs modulating the inflammatory process, namely inflamma-miRNAs. The expression of inflamma-miR-17-5p, -21-5p, -126-3p, and -146a-5p was analyzed in plasma samples from 116 patients with AD compared with 41 age-matched healthy control (HC) subjects. MiR-17-5p, miR-21-5p, and miR-126-3p plasma levels were significantly increased in AD patients compared to HC. Importantly, a strong inverse relationship was observed between miR-21-5p and miR-126-3p, and the cognitive impairment, assessed by Mini Mental State Examination. Notably, miR-126-3p was able to discriminate between mild and severe cognitive impairment. Overall, our results reinforce the hypothesis that circulating inflamma-miRNAs could be assessed as minimally invasive tools associated with the development and progression of cognitive impairment in AD.